FMRI functional connectivity of the periaqueductal gray in PTSD and its dissociative subtype. Issue 12 (20th September 2016) - Harricharan, Sherain; Rabellino, Daniela; Frewen, Paul A.; Densmore, Maria; Théberge, Jean; McKinnon, Margaret C.; Schore, Allan N.; Lanius, Ruth A.
Abstract: Background: Posttraumatic stress disorder (PTSD) is associated with hyperarousal and active fight or flight defensive responses. By contrast, the dissociative subtype of PTSD, characterized by depersonalization and derealization symptoms, is frequently accompanied by additional passive or submissive defensive responses associated with autonomic blunting. Here, the periaqueductal gray (PAG) plays a central role in defensive responses, where the dorsolateral (DL‐PAG) and ventrolateral PAG (VL‐PAG) are thought to mediate active and passive defensive responses, respectively. Methods: We examined PAG subregion (dorsolateral and ventrolateral) resting‐state functional connectivity in three groups: PTSD patients without the dissociative subtype ( n = 60); PTSD patients with the dissociative subtype ( n = 37); and healthy controls ( n = 40) using a seed‐based approach via PickAtlas and SPM12. Results: All PTSD patients showed extensive DL‐ and VL‐PAG functional connectivity at rest with areas associated with emotional reactivity and defensive action as compared to controls ( n = 40). Although all PTSD patients demonstrated DL‐PAG functional connectivity with areas associated with initiation of active coping strategies and hyperarousal (e.g., dorsal anterior cingulate; anterior insula), only dissociative PTSD patients exhibited greater VL‐PAG functional connectivity with brain regions linked to passive coping strategies and increased levels of depersonalization (e.g., temporoparietal junction; rolandic operculum). Conclusions: These findings suggest greater defensive posturing in PTSD patients even at rest and demonstrate that those with the dissociative subtype show unique patterns of PAG functional connectivity when compared to those without the subtype. Taken together, these findings represent an important first step toward identifying neural and behavioral targets for therapeutic interventions that address defensive strategies in trauma‐related disorders. Abstract : Posttraumatic stress disorder patients exhibited widespread periaqueductal gray functional connectivity during resting state, which may suggest the presence of greater defensive posturing at rest in these patients. Furthermore, those with the dissociative subtype of PTSD demonstrated unique functional connectivity patterns of the periaqueductal gray, with notable differences in connectivity between the dorsolateral and ventrolateral subdivisions.